Complication–simplification spiral in hygrothermal research. Issue 1 (5th January 2019) - Hokoi, Shuichi
Abstract: The author reviewed reported studies related to his own hygrothermal research. The outline of the research is first described with respect to the thermal conductivity of a moist porous material, linearity and nonlinearity, extension of research object, and human thermal physiology and psychology, followed by the lessons learned from these studies. Finally, some proposals for future studies are provided, based on the obtained knowledge. This review is based on a spiral development of thought in an ideal direction, that is, a simplification–complication spiral. Abstract : The author reviewed reported studies related to his own hygrothermal research. The outline of the researches is first described with respect to "thermal conductivity of moist porous material, " "linear and nonlinear, " "extension of research object, " and "human thermal physiology and psychology, " followed by the lessons learned from these researches. Finally, some proposals for future studies are provided, based on the obtained knowledge. The author tried to describe this review based on a spiral development of thought in an ideal direction, that is, a simplification–complication spiral.